Ghost ups her game [large type] - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries., 2021)
"After a busy morning dispatching emissaries from Heaven's Department of Good Intentions to those in need, Bailey Ruth Raeburn is feeling flush with success. So when an urgent call for help comes through from her old hometown, she can't resist taking on the mission herself. After all, what could go wrong? With the shouted warning of her boss, Wiggins - "Irregular! Problematic!" - ringing in her ears, she arrives to face a shocking scene: Professor Iris Gallagher leaning over the corpse of her colleague Matt Lambert, the murder weapon clutched in her hand. Bailey Ruth is only sent to help the innocent, but things are looking very black for Iris. With Wiggins breathing down her neck, and her old friend Police Chief Sam Cobb casting doubt on her every theory, Bailey Ruth must uncover the truth - or this could be the last trip to earth she's ever allowed to make"--